Electrical stimulation of the frontal cortex enhances slow-frequency EEG activity and sleepiness - D’Atri, A.; De Simoni, E.; Gorgoni, M.; Ferrara, M.; Ferlazzo, F.; Rossini, P.M.; De Gennaro, L. (Neuroscience, 2016)
•5Hz more than 0.8Hz anodal tDCS is effective in inducing EEG synchronization.•5Hz anodal tDCS as compared to sham induces an enhancement of sleepiness.•Cortical topography of delta EEG changes is regionally related to sleepiness. Our aim was to enhance the spontaneous slow-frequency EEG activity during the resting state using oscillating transcranial direct currents (tDCS) with a stimulation frequency that resembles the spontaneous oscillations of sleep onset. Accordingly, in this preliminary study, we assessed EEG after-effects of a frontal oscillatory tDCS with different frequency (0.8 vs. 5Hz) and polarity (anodal, cathodal, and sham). Two single-blind experiments compared the after effects on the resting EEG of oscillatory tDCS [Exp. 1=0.8Hz, 10 subjects (26.2±2.5years); Exp. 2=5Hz, 10 subjects (27.4±2.4years)] by manipulating its polarity. EEG signals recorded (28 scalp derivations) before and after stimulation [slow oscillations (0.5–1Hz), delta (1–4Hz), theta (5–7Hz), alpha (8–12Hz), beta 1 (13–15Hz) and beta 2 (16–24Hz)] were compared between conditions as a function of polarity (anodal vs. cathodal vs. sham) and frequency of stimulation (0.8 vs. 5Hz). We found a significant relative enhancement of the delta activity after the anodal tDCS at 5Hz compared to that at 0.8Hz. This increase, even though not reaching the statistical significance compared to sham, is concomitant to a significant increase of subjective sleepiness, as assessed by a visual analog scale. These two phenomena are linearly related with a regional specificity, correlations being restricted to cortical areas perifocal to the stimulation site. We have shown that a frontal oscillating anodal tDCS at 5Hz results in an effective change of both subjective sleepiness and spontaneous slow-frequency EEG activity. These changes are critically associated to both stimulation polarity (anodal) and frequency (5Hz). However, evidence of frequency-dependence seems more unequivocal than evidence of polarity-dependence.